On suspension of walls: towards a humanist agenda on marginality: Szabolcs Musca in conversation with Madalena Victorino. Issue 2 (3rd April 2019) - Musca, Szabolcs
ABSTRACT: This conversation traces the creation of Todos Festival, one of the most important international socially engaged multi-arts festivals in Southern Europe. In dialogue with artistic director, Madalena Victorino, the festival will be portrayed as a space for encounter and performative exploration of difference, linking marginalised migrant and minority communities to Lisbon's theatre scape and cultural ecology. We discuss modalities of transfiguring difficult (local) realities into performance on the interface between centres and peripheries.